Avaliação clínica, endoscópica e manométrica da deglutição em pacientes com miastenia grave autoimune adquirida - Oda, Adriana Leico [UNIFESP] (2002)
Dysphagia, or difficulty swallowing, is a common problem following myasthenia gravis (MG) and may lead to aspiration of saliva, food or liquids. We herein present 22 MG patients, with complaint of dysphagia, evaluated by phonoaudiological evaluation, nasofibrolaryngoscopical analysis and manometry of upper esophageal sphincter. The main objective was to evaluate the phases of the swallowing process and anatomical and functional aspects of oropharyngeal musculature. The age of patients varied from 19 to 74 years; being 19 female and 3 male. The main data were: (1) statistically significant relation between the phonoaudiological clinical evaluation and nasofibrolaryngoscopical one; (2) stomatognatical system disorders present in 100%; (3) swallowing and chewing disorders present in 100%, when clinically evaluated, and in 81,8% when evaluated by the nasofibrolaryngoscopy; (4) statistically significant relation between penetration/aspiration and antecedents of pneumonia; (5) stomatognatical muscles very altered, difficulty controlling the bolus, collection of food in the pharynx or larynx and presence of penetration and/or aspiration showed significant correlation with weakness of a pharyngeal muscles. These findings justify the necessity to evaluate clinically the swallowing phases in MG patients, with the main purpose to prevent both aspiration and dehidration from inadequate oral intake.